Satantango - Krasznahorkai, László (New Directions Pub. Corp., 2012)
"Set in an isolated hamlet, Satantango unfolds over the course of a few rain-soaked days. Only a dozen inhabitants remain in the bleak village, rank with the stench of failed schemes, betrayals, failure, infidelity, sudden hopes, and aborted dreams. At the center of Satantango is the eponymous drunken dance."--P. [i].